2012
DOI: 10.1038/ajg.2012.332
|View full text |Cite
|
Sign up to set email alerts
|

Major Complications of Pneumatic Dilation and Heller Myotomy for Achalasia: Single-Center Experience and Systematic Review of the Literature

Abstract: Background & Aims Pneumatic dilation (PD) and laparoscopic Heller myotomy (LHM) can be definitive therapies for achalasia; recent data suggest comparable efficacy. However, risk must also be considered. We reviewed the major complication rate of PD and LHM in a high volume center and reviewed the corresponding literature. Methods We reviewed 12 years of our institution’s achalasia treatment experience. During this interval a consistent technique of PD was used utilizing Rigiflex dilators. Medical records wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 70 publications
4
76
0
1
Order By: Relevance
“…Considering that the cost of pneumatic dilation is substantially less than LHM and that the risk of oesophageal perforation between techniques is comparable (about 1% when performed by gastroenterologists with extensive experi ence with the procedures) 58 , these findings argue for pneumatic dilation as the preferred initial treatment for type II achalasia.…”
Section: Box 2 | Open Research Questionsmentioning
confidence: 98%
“…Considering that the cost of pneumatic dilation is substantially less than LHM and that the risk of oesophageal perforation between techniques is comparable (about 1% when performed by gastroenterologists with extensive experi ence with the procedures) 58 , these findings argue for pneumatic dilation as the preferred initial treatment for type II achalasia.…”
Section: Box 2 | Open Research Questionsmentioning
confidence: 98%
“…In contrast, other authors reported no differences in complications rate or the degree of surgical difficulty, but similar outcomes after myotomy in patients with prior failed PD or Botulinum toxin injection (66,67). In fact, surgical complication rates are thought to be more dependent on surgeon experience and the incidence of previous esophageal surgery than on prior botulinum toxin injection or prior pneumatic dilatation (68).…”
Section: Heller Myotomymentioning
confidence: 50%
“…In addition, several authors have also reported similar patient outcomes after myotomy even after prior failed pneumatic dilation or Botulinum toxin injections Surgery after botulinum toxin injections has been suggested to be more difficult because of a marked fibrotic reaction that can develop at the gastroesophageal junction that obliterates surgical planes (62)(63)(64)(65). Nevertheless, some authors have reported similar outcomes in this situation to those of a primary procedure (66)(67)(68).…”
Section: Heller Myotomymentioning
confidence: 78%
See 2 more Smart Citations